CA 125 Immunosensor Based on Poly‐Anthranilic Acid Modified Screen‐Printed Electrodes. Issue 1 (13th November 2012) - Taleat, Zahra; Ravalli, Andrea; Mazloum‐Ardakani, Mohammad; Marrazza, Giovanna
Abstract In this paper, two simple and sensitive approaches for CA 125 detection are presented by using antibody immobilized on poly‐anthranilic acid modified graphite screen‐printed electrodes. The first proposed approach is a label‐free impedimetric immunosensor. The immunoassay is based on poly‐anthranilic acid (PAA) modified graphite screen‐printed electrodes with subsequent covalently monoclonal antibody anti‐CA 125 immobilization. The modified screen‐printed electrodes are used to capture the protein from the sample solutions. A curve calibration by electrochemical impedance spectroscopy (EIS) was obtained. The second approach is based on a sandwich format. The monoclonal anti‐CA 125 antibodies immobilized on poly‐anthranilic acid modified graphite screen‐printed electrodes is used to capture the protein from the sample solution. The sandwich assay is then performed by adding secondary anti‐CA 125 antibodies labeled with gold nanoparticles (AuNPs). The antibody‐AuNPs captured onto immunosensor surface induced the silver deposition from a silver enhancer solution. The deposited AgNPs could be measured by anodic stripping analysis (ASV) in acid solution. A curve calibration by ASV was obtained. The experimental conditions were examined and were optimized using electrochemical impedance spectroscopy. The performance of both immunosensors in terms of sensitivity, reproducibility and selectivity were studied.